Consumidores ou cidadãos? : questões éticas nos discursos sobre a proteção de dados pessoais na cidade de São Paulo - Dainezi, Gustavo Fernandes Americo (2019)
This research studied the discourses about data protection that were pronounced in the city of São Paulo in public events held throughout 2018. We verified that, culturally, two main understandings on the subject take center stage in the global debate around data protection – the American and the European – and that each of them is clearly grounded in a different moral paradigm (utilitarianism and deontology, respectively). We proposed, then, a Critical Discourse Analysis methodology in order to verify if, in the local contexto analyzed, these two paradigms replicate and how so. After analyzing the empirical data collected, we were able to assess their presence, but with considerable modulation, motivated by specific socio-historic conditions.